Antioxidant activity of rosemary essential oil fractions obtained by molecular distillation and their effect on oxidative stability of sunflower oil - Mezza, Gabriela Natalia (2018)
The objective of this study was to evaluate the antioxidant activity of rosemary essential oil fractions obtained by molecular distillation (MD) and investigate their effect on the oxidative stability of sunflower oil. MD fractions were prepared in a series of low-pressure stages where rosemary essential oil was the first feed. Subsequently, a distillate (D1) and residue (R1) were obtained and the residue fraction from the previous stage used as the feed for the next. The residue fractions had the largest capacity to capture free radicals, and the lowest peroxide values, conjugated dienes and conjugated trienes. The antioxidant activity of the fractions was due to oxygenated monoterpenes, specifically α-terpineol and cis-sabinene hydrate. Oxidative stability results showed the residues (R1 and R4) and butylated hydroxytoluene had greater antioxidant activity than either the distillate fractions or original rosemary essential oil. The residue fractions obtained by short path MD of rosemary essential oil could be used as a natural antioxidants by the food industry.